2019
DOI: 10.1186/s13104-019-4496-5
|View full text |Cite
|
Sign up to set email alerts
|

Level of physical activity and associated factors during pregnancy among women who gave birth in Public Zonal Hospitals of Tigray

Abstract: Objectives Physical activity in the general population is considered too low, and this is true for pregnant women. Moderate physical activity during pregnancy have many benefits for the mother and the developing baby. This study was aimed to assess the level of physical activity during pregnancy and associated factors in public zonal hospitals of Tigray, Ethiopia. A hospital based cross-sectional study was used and 458 study participants was selected using multistage sampling technique. The data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
70
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(85 citation statements)
references
References 30 publications
13
70
2
Order By: Relevance
“…This study found that about 30% of the pregnant women practiced exercise during pregnancy, nonetheless, only 11.7% among the overall sample and 37.9% among those who practiced exercise had adequate practice in accordance with the minimum recommended guidelines for this group [1,17]. This is almost similar to the ndings of two regional studies reporting about level of physical activity during pregnancy [20,30]. However, this is much lower than the practice of exercise reported in Nigeria (84.7%), Canada (29%), and Brazil (29%) in a similar population [28,31,36].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This study found that about 30% of the pregnant women practiced exercise during pregnancy, nonetheless, only 11.7% among the overall sample and 37.9% among those who practiced exercise had adequate practice in accordance with the minimum recommended guidelines for this group [1,17]. This is almost similar to the ndings of two regional studies reporting about level of physical activity during pregnancy [20,30]. However, this is much lower than the practice of exercise reported in Nigeria (84.7%), Canada (29%), and Brazil (29%) in a similar population [28,31,36].…”
Section: Discussionsupporting
confidence: 77%
“…Studies report that most of the pregnant women living in lowmiddle income countries (LMICs) are not su ciently active and did not meet the present exercise guidelines during their pregnancy. The prevalence of sedentary activity is high among Ethiopian pregnant women (76, 79%) and the majority of them are below par with the ACOG recommendations [19][20][21]. Despite physical activity and antenatal exercises are not threatening according to the current guidelines, this population's behavior does not seem to change [17].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, most women do not meet the 150 min per week PA recommendation by specialised bodies and institutions. Previous studies have reported the prevalence of prenatal inactiveness with variations across countries as follows: Serbia (27.2%) [6], USA (25%) [7], China (45.15%) [8], Ethiopia (21.9%, 8.4%) [9,10], Nigeria (10.2%, 13.6%) [11,12] and Norway (14.6%) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the substantial evidence on the benefits of PA during pregnancy, studies have reported a considerable decline in PA among pregnant women in both developed [47][48][49][50] and developing countries [6,9,10,[51][52][53][54][55], with varying degrees of participation shaped by context-specific paradigms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation